Ureterolitotomía endoscópica láser en el manejo de cálculos ureterales grandes (2020)
Introduction: Urolithiasis is a pathology with high prevalence worldwide, this leads to a high volume of surgical procedures. The management of choice for ureteral stones is semi-rigid or flexible ureteroscopy (URS / FURS) and Holmium laser lithotripsy in most cases. Objectives: To define the results, risks and complications of Holmium laser endoscopic ureterolithotomy for ureteral stones ≥1.5 cm. Materials and methods: Descriptive cross-sectional study in patients with ureteral stones ≥1.5 cm, led to endoscopic ureterolithotomy with Holmium laser in a medical center specialized in urolithiasis from January 1, 2009 to December 31, 2017. Results: 1444 Holmium laser lithotripsies were performed in the analyzed period, 43 of these procedures in ureteral stones ≥ 1.5 cm. The stone-free rate was 67.4%, average surgery time 64.7 minutes, reoperation rate 9.3% and complications 9.3%. There was no statistically significant difference in complications and stone-free rate between 1.5-1.9 cm and ≥2 cm, however, the reintervention rate for stones ≥2cm was 23.5%, greater than those <2 cm 0% p 0.009. Conclusions: Urethral stones ≥1.5 cm are rare, the outcomes after surgical management with URS / FURS appear to be worse in stones ≥2cm.